Research in technology education: looking back to move forward … again - Williams, John (Kluwer Academic Publishers, 2015)
In 2013 I published, in this Journal, a review of journals and conference publications in Technology Education from 2006 to 2010 as one measure of the nature of research that was being conducted in the area (Williams in Int J Technol Des Educ 23(1):1–9, 2013). An element of that review was a prediction of trends, from the findings, to speculate about what research areas may develop and become more significant and more common in the future. This prediction was integrated with personal experiences and understandings to result in a speculative discussion of future trends. This Research Note represents an extended review, both in terms of the journals and conferences covered, and the time period to include 2011–2013, in order to evaluate those predictions and refine possible future trends, and to answer the research question:What are the developments and trends in Technology Education research? It is hoped that this will be useful to researchers in the area of Technology Education who are planning research, and to stimulate discussion about the research that is needed in this area.